Sosialisasi Pemasaran Berbasis E-Commerce pada Home Industri di Desa Mergotentrem Kabupaten Oku Timur - Vovi Sinta; Muhamad Nanang Rifa’i; Sigit Priyono (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This service activity is carried out in the form of socialization by providing knowledge, understanding related to marketing methods to the Margotentrem village community regarding products produced by the bamboo craftsman home industry with the hope of being able to develop and become a competitive business in the midst of modern business today and in the future. Methodology: This research is a qualitative descriptive study using survey methods and Participatory Rural Appraisal Method (PRA) in which the respondents are home industry bamboo manufacturers in Margotentrem village who are directly involved starting from the process of identifying problems, identifying needs, planning, implementing, to monitoring and evaluating activities. Results: From the realization of this service activity, it is able to provide solutions, be able to introduce products that are characteristic of one of the ethnic groups in Indonesia, and be able to provide value for products produced by the home industry of bamboo craftsmen by utilizing e-commerce through accounts, Facebook, Instagram, Shopee and Tokopedia. Limitations: The implementation of this service only focuses on socializing methods for marketing products produced by the home industry of bamboo craftsmen but is contrary to understanding, interest and limited human resources. Contribution: Providing solutions and adding technology-based knowledge, especially in the field of digital marketing.